Pharmacotherapy of infertility in Ghana: retrospective study at the cape coast teaching hospital - Stephen Mensah Arhin; Kwesi Boadu Mensah; Evans Agbeno; Vitus Sambo Badii; Charles Ansah (Taylor & Francis Group, 2019)
Background Infertility is a major challenge for couples globally. Due to low income levels and the high cost of other assisted reproductive techniques, pharmacotherapy remain the major first line treatment option for infertility in Sub-Saharan Africa. Objective The aim of this study was to assess the prevalence of infertility as well as the effectiveness and success achieved following infertility pharmacotherapy at the Cape Coast Teaching Hospital in Ghana. Methods This study was a retrospective observational study of 825 couples attending infertility clinic at the hospital. Results Prevalence of infertility at the study center was estimated to be 12.3%. Treatment mainly involved the use of clomiphene citrate, antioxidants, herbo-mineral drugs (Ayurveda), multivitamin and antibiotics. Pharmacotherapy resulted in successful conception in one out of every five couples (19.4%; n = 160). Secondary infertility, although more prevalent in the study population (44.8%; n = 370), had lower conception rates during pharmacotherapy than primary infertility (15% vs 26.2%). Age, kind of infertility, employment status but not educational level were significantly associated with pharmacotherapy success. In ovulation induction, clomiphene citrate plus folic acid and vitamin E adjuncts improved ovulation rates during cycle treatments compared to clomiphene citrate alone. Pharmacotherapy of idiopathic infertility (39%, n = 323) was a major challenge with very limited success rates. Interestingly, it was noted that treating couples or female partners only for idiopathic infertility resulted in higher success rates than treating the male partner only. Again, 90-day treatment regimen doubled conception rates when compared with corresponding 30-day treatment regimen. However, zinc sulfate even in short term treatment regimens (30 days) enhanced conception rates in idiopathic infertility. Conclusions Prevalence of infertility was estimated to be about 12.3%. One out of every five infertile couples achieved success with pharmacotherapy. Factors such as age, type of infertility, employment status, but not education were significantly associated with treatment success.